An experimental study of charge diffusion in the undepleted silicon of X-ray CCDs. - Prigozhin, G.
We have experimentally studied the diffused electron clouds formed by X-ray photons interacting within the undepleted bulk of silicon beneath the depleted region of an X-ray CCD. Usually, such events are spread over multiple pixels and are often rejected in data analysis because of incomplete charge collection in the undepleted bulk. An unusual CCD clocking mode where every 100 sequential rows were summed in the serial register allowed us to reduce the charge distribution to a one-dimensional (1-D) representation without losing any information, resulting in a dramatically simplified analysis and improved signal/noise ratio. We have shown that events from the undepleted bulk can be used for retrieving information regarding the energy of the corresponding X-ray photon. In our study, the Mn Kα and Kβ lines emitted by the radioactive Fe55 source could be clearly separated. Such an analysis can markedly improve the sensitivity of partially depleted CCDs at higher energies. By averaging many events that originate at the same distance from the surface of the device, we were able to extract the shape of the charge cloud after the completion of the diffusion process. The results were found to be in good agreement with theoretical predictions.
Keywords: 2048 pixel; 4096 pixel; 8388608 pixel; Si; X-ray CCDs; X-ray photon energy information retrieval; Charge cloud shape; Charge diffusion; Depleted region; Diffused electron clouds; Diffusion length; Incomplete charge collection; One-dimensional representation; Partially depleted CCD sensitivity; Serial register; Signal/noise ratio; Undepleted Si bulk; Unusual CCD clocking mode; Mn Kα lines; Mn Kβ lines; Radioactive Fe55 source